First record of the family Diplommatinidae Gray, 1847 (Gastropoda: Architaenioglossa) from Ecuador with description of a new Adelopoma Doering, 1885 - Greķe, Kristīne; Kagainis, Uģis; Telnov, Dmitry (Zootaxa, 2023)
Diplommatinidae Gray, 1847, a family of minute cyclophoroid gastropods, is recorded from Ecuador for the first time. Adelopoma gracile Greķe, sp. nov. is described and illustrated from River Pastaza valley, central Ecuador. Differential diagnosis is provided for similar congeners. An annotated checklist of and a preliminary key to the Adelopoma Doering, 1885 species are provided.